Penurunan Kadar Sianida Dengan Pengolahan Sistim Oksidasi Pada Industri Pelapisan Logam - Siti Agustina; Emmy Ratnawati (Jurnal Kimia dan Kemasan, 2000)
It's common that the waste water from electroplating industry contains heavy metals such as cyanide. Based on this research, reduction of cyanide content from electroplating waste water is conducted by CN and CNO oxidations with sodium hypochlorite as an oxidator. The result-of this research shown that the optimum condition for CN oxidations is on pH 10.5, reaction time 6 minutes which resulting CN reduction 98,6%, while the CNO oxidations is on pH 8. 0, reaction time 15 minutes. By process of oxidations, coagulations, sedimentations and filtrations the CN content from electroplating wastewater can be reduced from 3 0 mg!! to 0. 004 mg/! to fulfill waste water quality standard for electroplating industry maximum 0. 05 mg/!.